Pertanggungjawaban Pidana Terhadap Mucikari Dalam Tindak Pidana Prostitusi - Ramadhina Krisna Manggala Putra; Aryo Fadlian; Margo Hadi Pura (Peneliti.net, 2022)
Prostitution is a problem that does not only involve prostitutes, but more than that, it is an activity that involves many people such as pimps, brokers, and consumers, most of whom are men who often escape the attention of law enforcement officials. Juridical problems can be seen where punishment can only be carried out for pimps or pimps (pimp) while prostitutes and their clients cannot be subject to criminal charges. To find answers to these problems, this research uses a type of normative legal research that is descriptive analytical, where this normative legal research uses secondary data as the main data by using data collection techniques carried out by means of library research (library research), and data analysis using this method. qualitative data analysis. This data analysis is intended to be based on an overview, the facts obtained will be analyzed carefully to answer the problem. The regulation of criminal law against perpetrators of criminal acts of prostitution is regulated in several laws and regulations, namely Article 296 of the Criminal Code, Article 506 of the Criminal Code, Article 2 Paragraph (1) of Law Number 21 of 2007 concerning Eradication of the Crime of Trafficking in Persons, and Article 30 in conjunction with Article 4 Paragraph (2) of Law Number 44 of 2008 concerning pornography